Analysis of perceived stress, cardiovascular and central nervous system changes before and after menstruation in the age group 18-22 years - Pardeshi, Amita M. (International Journal of Research in Medical Sciences, 2017)
Background: Premenstrual syndrome is a set of physical, behavioural or emotional symptoms that some women experience on regular basis in relation to menstruation. Premenstrual symptoms have been associated with perceived stress, and perceived stress is the strongest predictor of premenstrual syndrome. The purpose of this study was to investigate the premenstrual stress and its effect on cardiovascular system and sensorimotor association and processing capability of central nervous system. Methods: The present study was done in 60 healthy female volunteers in age group of 18-22 years. We measured following parameters during premenstrual and postmenstrual phases- pulse rate, blood pressure, weight, auditory and visual reaction time and perceived stress with the help of Cohen’s perceived stress scale. Results: The study revealed that significant increase was observed in perceived stress, pulse rate, blood pressure, weight, auditory reaction time (ART), and visual reaction time (VRT) during premenstrual period as compared to postmenstrual period. Conclusions: These changes could be attributed to fluid and salt retention due to ovarian steroids and to exaggerated response to hormonal changes leading to decrease in the processing capability of central nervous system. It is not clear how stress may contribute to increased pre-menstrual symptom severity, although stress-induced changes in ovarian hormone levels and neurotransmitters may be involved.